Lessons learned in NWCOS: success and consensus in collaboration process - Casterson, Jeremy, author (Colorado State University. Libraries, 2009)
The Northwest Colorado Stewardship (NWCOS) is an inactive collaborative group based out of Craig, Colorado and comprised of a wide variety of stakeholder participants. NWCOS dealt with a wide range of issues and core points of conflict included oil and gas development, wilderness designation proposals, grazing and wildlife habitat. NWCOS was unable to achieve its primary goal of crafting a consensus community alternative to the U.S. Bureau of Land Management's Resource Management Plan for the Little Snake Resource area. Despite its failure at reaching this goal, NWCOS had many other successes such as decisions about protocols, improved relationships and communication. NWCOS was broad in scope and stakeholdership, and participants feel both frustration as well as benefits from the process of engaging in the collaboration. We will use this session to explore the major lessons learned for NWCOS and how they might be applicable to other similar collaborative efforts. Lessons learned from a federal agency will be shared as well as perspectives from both a research and agency standpoint.
Lessons learned from difficult collaborations: the northwest Colorado stewardship
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. The presenter is affiliated with Bureau of Land Management, Little Snake Field Office.
Keywords: Northwest Colorado Stewardship; NWCOS; collaborative conservation